Spatial Variability Study of Duty Cycle in GSM 900 and 1800 MHz Bands in Rural and Urban Environments - Nasir Faruk; Y Imam-Fulani; I A Sikiru; A A Oloyede; Q R Adebowale; L A Olawoyin; Abubakar Abdulkarim; Y A Adediran (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2019)
This paper examines the spatial variability of duty cycle in the GSM 900 and 1800 MHz bands within Kwara State, Nigeria. The results show spatial variance in the duty cycle with average occupancies of 1.67%, 17.76%, 10.55% and 0.39%, 11.00% and 5.11 in the rural, urban and all locations for 900 and 1800 MHz bands. Findings also show that there is very high positive correlation between rural 900/1800 MHz and urban 900/1800 MHz. But very high negative correlations exits between urban 900 and rural 1800, and urban 1800 and rural 1800. There is a weak and negative correlation between rural and urban 900 MHz, rural-urban 1800. These results clearly showthe abundance of unutilised spectrum within the GSM bands. Therefore, regulatory commissions should adopt flexible spectrum reuse strategy to relax the regulatory bottlenecks to maximize the scarce radio resources in the licensed bands, especially for rural network deployments